2005
DOI: 10.3201/eid1102.041016
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Host-Cell Susceptibility to Usutu Virus

Abstract: We investigated the susceptibility to Usutu virus ( Flavivirus ) of 13 permanent cell lines, 3 primary cell cultures, and chicken embryos. Vero, PK-15, and goose embryo fibroblast cells developed cytopathic effects; however, viral multiplication was detected in all mammalian cell types by immunohistochemical tests. Chicken embryo fibroblast cells and chicken embryos were resistant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 4 publications
(4 reference statements)
4
41
0
6
Order By: Relevance
“…The tissue samples were homogenized and suspended in phosphatebuffered saline. After centrifugation (4,000 ϫ g, 10 min), the supernatants were inoculated onto 1-day-old, confluent primary goose embryo fibroblast cell cultures (2). The cell cultures were incubated at 37°C for 3 to 5 days and were checked daily for the occurrence of cytopathic effects (CPEs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue samples were homogenized and suspended in phosphatebuffered saline. After centrifugation (4,000 ϫ g, 10 min), the supernatants were inoculated onto 1-day-old, confluent primary goose embryo fibroblast cell cultures (2). The cell cultures were incubated at 37°C for 3 to 5 days and were checked daily for the occurrence of cytopathic effects (CPEs).…”
Section: Methodsmentioning
confidence: 99%
“…An extended outbreak was observed in the subsequent year in the same area and predominantly involved blackbirds (Turdus merula) (15), which indicated that USUV survived the Austrian winter and adapted to the local mosquito populations. Detailed investigations were carried out, including the genetic characterization of the emerging USUV strain (1) and host susceptibility studies (2,6,7), in order to assess the ecological and epidemiological impacts of the virus. A dead bird surveillance program was introduced in Austria to monitor the occurrence and spread of the infection (8).…”
mentioning
confidence: 99%
“…Unterschiedliche Empfäng-lichkeiten für die Infektion von Zellkulturen verschiedener Spezies wurden beobachtet. Einige Zellen wie Vero (Nierenzellen der Grünen Meerkatze), PK15 (Nierenzellen des Schweins) und emb-ryonale Gänsefibroblasten entwickelten einen ausgeprägten zytopathischen Effekt, während andere Zellen, unter anderem auch Helazellen, sich zwar infizieren ließen, aber keine zytopathogenen Veränderungen zeigten [60]. Inwieweit eine neu etablierte Zelllinie aus der Rötelmaus (Myodes glareolus) besonders für die Isolierung von USUV geeignet ist, muss weiter untersucht werden [61].…”
Section: Serologischer Nachweisunclassified
“…Für die Untersuchung des Zelltropismus wurde das österreichische Isolat aus einer Amsel verwendet, das auf Verozellen angezüchtet worden war. Keine Virusvermehrung wurde in Hühnerembryofibro-blasten oder im embryonierten Hühner-ei gefunden [47,60].…”
Section: Serologischer Nachweisunclassified
“…33 Later on, the susceptibility to USUV infection was assessed in various cell lines and cultures, including HeLa (human), Vero (simian), ED (equine), PK-15 (porcine), RK-13 (rabbit), MDBK (bovine), MDCK (canine), DK (canine), CR (feline), BHK-21 (hamster), BF (hamster), C6 (rat), TH1 (turtle), primary goose embryo fibroblasts, and horse kidney cells. 34 Although replication was detected in all mammalian cell types, only Vero, PK-15, and goose embryo fibroblast cells developed cytopathic effects. Rodent cell lines derived from the bank vole were also susceptible to infection with USUV.…”
Section: Host Cell-virus Interactionsmentioning
confidence: 99%